2017
DOI: 10.18632/oncotarget.20413
|View full text |Cite
|
Sign up to set email alerts
|

Let-7d increases ovarian cancer cell sensitivity to a genistein analog by targeting c-Myc

Abstract: c-Myc is a key oncogenic transcription factor that participates in tumor pathogenesis. In this study, we found that levels of c-Myc mRNA and protein were higher in early ovarian cancer tissues than normal ovary samples. Increased c-Myc levels correlated positively with clinical stage I (Ia+b/Ic) in ovarian cancer patients. Patients with higher nuclear c-Myc expression had shorter overall survival times than patients with low c-Myc expression. Knocking down c-Myc sensitized ovarian cancer cells to 7-difluoromet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 34 publications
1
17
0
Order By: Relevance
“…Ning Y, et al, found that let-7d was downregulated in ovarian cancer tissues compared with normal ovarian tissues [22]. Let-7d was also reported to be downregulated in oral squamous cell carcinoma [33] and renal cell carcinoma [24], which was consistent with our results in breast cancer.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Ning Y, et al, found that let-7d was downregulated in ovarian cancer tissues compared with normal ovarian tissues [22]. Let-7d was also reported to be downregulated in oral squamous cell carcinoma [33] and renal cell carcinoma [24], which was consistent with our results in breast cancer.…”
Section: Discussionsupporting
confidence: 91%
“…Let-7 family, including let-7d, was reported to inhibit tumor pathogenesis [20,22]. On the other hand, let-7d contributes to the pathogenesis of some cancers.…”
Section: Introductionmentioning
confidence: 99%
“…As the inhibition of PIM2 increases, expression of cMyc protein reduces in the OC cells [ 13 ]. On the other hand, recently, knocking down of cMyc caused reduction of the PI3K/AKT signaling pathway in OC cells [ 82 ] which is opposite to as reported in normal cells [ 83 ]. This data suggests the involvement of PI3K, PIM kinases and cMyc together in OC cells but further studies to probe mechanistic approach will help to understand exact relationship between them.…”
Section: Pim Kinases and Proteins Involved In Cellular Functions Omentioning
confidence: 83%
“…We have previously confirmed that a genistein analog can suppress PI3K/AKT signaling5 and the FoxO signaling pathway 68. With advances in genomics, network analysis could help dissect multiple human diseases.…”
Section: Introductionmentioning
confidence: 70%